Analisis Peran Website E-Commerce Koperasi Pelita Desa dan Supply Chain Management dalam Meningkatkan Nilai Tambah Bisnis Industri Koperasi Modern - Hidayat, Udin (STIE Bangkinang Publishing, 2023)
The use of web-based e-commerce technology is changing aspects of people's lives, including cooperatives. Cooperatives are making a comeback and transforming into modern businesses and industries, thanks to digitalization. Cooperative governance management, including the supply chain, is key in modern cooperatives. The use of e-commerce website technology, such as Pelita Desa Cooperative, is important to the success of cooperatives. The application of supply chain management and innovation through e-commerce website technology aims to create added value in the cooperative industry. This research uses qualitative and quantitative methods with interviews and data analysis. Zoom Meeting was chosen for cost and time efficiency. Data analysis involved supply chain management and value-added calculation with Hayami Calculation Theory. Interview data and data interpretation were used to supplement the information. This research understands the role of Pelita Desa Cooperative's e-commerce website technology and supply chain management in increasing the added value of modern cooperative businesses.